Excess long-term mortality following non-variceal upper gastrointestinal bleeding: a population-based cohort study - Crooks, Colin John; Card, Timothy R.; West, Joe (Public Library of Science, 2013)
Background It is unclear whether an upper gastrointestinal bleed is an isolated gastrointestinal event or an indicator of a deterioration in a patient's overall health status. Therefore, we investigated the excess causes of death in individuals after a non-variceal bleed compared with deaths in a matched sample of the general population. Methods and Findings Linked longitudinal data from the English Hospital Episodes Statistics (HES) data, General Practice Research Database (GPRD), and Office of National Statistics death register were used to define a cohort of non-variceal bleeds between 1997 and 2010. Controls were matched at the start of the study by age, sex, practice, and year. The excess risk of each cause of death in the 5 years subsequent to a bleed was then calculated whilst adjusting for competing risks using cumulative incidence functions. 16,355 patients with a non-variceal upper gastrointestinal bleed were matched to 81,523 controls. The total 5-year risk of death due to gastrointestinal causes (malignant or non-malignant) ranged from 3.6% (≤50 years, 95% CI 3.0%–4.3%) to 15.2% (≥80 years, 14.2%–16.3%), representing an excess over controls of between 3.6% (3.0%–4.2%) and 13.4% (12.4%–14.5%), respectively. In contrast the total 5-year risk of death due to non-gastrointestinal causes ranged from 4.1% (≤50 years, 3.4%–4.8%) to 46.6% (≥80 years, 45.2%–48.1%), representing an excess over controls of between 3.8% (3.1%–4.5%) and 19.0% (17.5%–20.6%), respectively. The main limitation of this study was potential misclassification of the exposure and outcome; however, we sought to minimise this by using information derived across multiple linked datasets. Conclusions Deaths from all causes were increased following an upper gastrointestinal bleed compared to matched controls, and over half the excess risk of death was due to seemingly unrelated co-morbidity. A non-variceal bleed may therefore warrant a careful assessment of co-morbid illness seemingly unrelated to the bleed.